2019
DOI: 10.1038/s41431-019-0353-1
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous decision-making for antenatal screening in Pakistan: views held by women, men and health professionals in a low–middle income country

Abstract: Prenatal genetic technologies now are being implemented in LMICs and while there is much research on the ethical, legal and social implications of such technologies in Western countries, there is a paucity of such research in LMICs, which have diverse cultural, religious, political, financial and health service contexts. This study aimed to explore views about women's autonomous decision-making for antenatal screening held by women, men and healthcare professionals (HCPs) in Pakistan. A Q-methodology study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
5
11
0
Order By: Relevance
“…This is in line with the conclusions in several studies that show the role of husband/partner in providing support for a woman's health behavior [30--33]. Some other studies actually involve a husband to be able to improve a woman's health status through actively better health behaviors [34][35].…”
Section: Discussionsupporting
confidence: 88%
“…This is in line with the conclusions in several studies that show the role of husband/partner in providing support for a woman's health behavior [30--33]. Some other studies actually involve a husband to be able to improve a woman's health status through actively better health behaviors [34][35].…”
Section: Discussionsupporting
confidence: 88%
“…This is in line with the findings of several studies that have shown the role of a husband/partner in providing support for a woman's healthy lifestyle [32][33][34][35]. Some other studies actually encourage a husband to help improve a woman's health status by actively encouraging a healthier lifestyle [36,37].…”
Section: Discussionsupporting
confidence: 88%
“…The purpose of this study is to explore women's understandings of informed choice concerning antenatal screening tests in two different societal contexts in China. The findings show that women interpret informed choice in different ways, supporting the results of past studies 5,23,27 . We found five viewpoints in our study.…”
Section: Discussionsupporting
confidence: 91%
“…People may not recognize them as independent decision makers 26 . For example, women from South Asia may prefer to follow the doctor's or husband's advice 5,27 and not make decisions themselves 21,22 . Previous research has also shown that Chinese women prefer to make an informed choice with their husband and family and want doctors to provide directive advice 23,28 .…”
Section: Introductionmentioning
confidence: 99%